Enhanced Visual Degradation Deep Learning Method for Video Encryption and Decryption - V Jayabharathi,; Dr. S. Sukumaran, (The Bioscan, 2024)
Numerous businesses have developed proprietary or selective encryption techniques for communication and data collection. Because online fraud and cyber theft are on the rise, protecting sensitive data is becoming more and more important. Visual cryptography is a widely used cryptographic technique that involves concealing visual data, such as text, images, videos, and audio, so that only authorized groups with full access to the encrypted data can decrypt it and reveal the original content either collectively or individually. Conduct a number of security tests, including information entropy, mean square error, temporal complexity, histograms, number of pixel change ratio, peak signal-to-noise ratios, and many more, in order to assess the security and resilience of these suggested methods. The study examines video encryption and encoding approaches and uses a variety of assessment metrics to demonstrate that propose method is effective for video encrypting and decrypting.